Overexpression of the auxin binding protein1 modulates PIN-dependent auxin transport in tobacco cells - Čovanová, Milada; Sauer, Michael; Rychtář, Jan; Friml, Jiří; Petrášek, Jan; Zažímalová, Eva (PLoS One, 2013)
BACKGROUND: Auxin binding protein 1 (ABP1) is a putative auxin receptor and its function is indispensable for plant growth and development. ABP1 has been shown to be involved in auxin-dependent regulation of cell division and expansion, in plasma-membrane-related processes such as changes in transmembrane potential, and in the regulation of clathrin-dependent endocytosis. However, the ABP1-regulated downstream pathway remains elusive. METHODOLOGY/PRINCIPAL FINDINGS: Using auxin transport assays and quantitative analysis of cellular morphology we show that ABP1 regulates auxin efflux from tobacco BY-2 cells. The overexpression of ABP1can counterbalance increased auxin efflux and auxin starvation phenotypes caused by the overexpression of PIN auxin efflux carrier. Relevant mechanism involves the ABP1-controlled vesicle trafficking processes, including positive regulation of endocytosis of PIN auxin efflux carriers, as indicated by fluorescence recovery after photobleaching (FRAP) and pharmacological manipulations. CONCLUSIONS/SIGNIFICANCE: The findings indicate the involvement of ABP1 in control of rate of auxin transport across plasma membrane emphasizing the role of ABP1 in regulation of PIN activity at the plasma membrane, and highlighting the relevance of ABP1 for the formation of developmentally important, PIN-dependent auxin gradients.
Keywords: Neural Networks, Computer; Female; Cognitive Dysfunction; Cell Physiological Phenomena; Brain Mapping; ženské pohlaví; longitudinální studie; Positron-Emission Tomography; fyziologie buňky; fluorodeoxyglukosa F18; neurozobrazování; lidé; studie případů a kontrol; Aged, 80 and over; následné studie; mapování mozku; Follow-Up Studies; Male; Case-Control Studies; Aged; glukosa; Alzheimer Disease; neuronové sítě; Glucose; kognitivní dysfunkce; Alzheimerova nemoc; lidé středního věku; pozitronová emisní tomografie; senioři nad 80 let; Fluorodeoxyglucose F18; senioři; mužské pohlaví; Middle Aged; Neuroimaging; Longitudinal Studies; Humans